Callus Regeneration of Gynura procumbens (Lour.) Merr. In Vitro - syahid, Sitti Fatimah; Seti, Lusia (Jurnal Biologi Universitas Andalas, 2022)
Gynura procumbens (Lour.) Merr. is one of the species of Asteraceae which is potential as medicinal. Propagation of the species could be conducted by vegetative, so the plant genetic variability is narrow. Genetic variability could be increased by somaclonal variation through callus culture. There is no report on in vitro regeneration from callus culture, although this method could assist further genetic improvement of plants. In this experiment, different concentrations of 2,4- D (0.1 ; 0.3 ; 0.5 mg L -1 ) singly or combination with BA (0.1 ; 0.3 and 0.5 mg L -1 ) were evaluated for callus induction and several concentrations of BA (0 ; 0.1; 0.5 and 1.0 mg -1 ) combination with kinetin (0.1 and 0.3 mg-1) were observed for ability of callus formed shoots. The results showed that the best media for callus induction was 0.5 mg L -1 2,4-D + 0.5 mg L -1 BA. This treatment produced friable callus structure, no roots and yellowish white. Callus regeneration was obtained on the combination of 0.1 mg L -1 BA. + 0.1 mg L -1 kinetin and 0.1 mg L -1 BA + 0.5 mg L -1 kinetin but the percentage was still low.Â Keywords: G procumbens Lour. Merr, induction, regeneration, calli, in vitro